Peer Group Influence, Socio-Economic Background and Gender Differentiating Psychological Well-Being among Adolescents of Senior Secondary Schools in Ogun State - Ogunsanwo, Mojisola A. (NIU Journal of Humanities; Vol 5 No 1 (2020): KIU Journal of Humanities, Vol. 5 No. 1, March 2020, 2020)
The concern for proper adolescents’ psychological well-being is to ensure that children are properly integrated into healthy family in which young people will thrive, translating into a healthier society. In view of this, this study investigated and reported the social factors differentiating psychological well-being of Senior Secondary School adolescents in Ogun State. A survey research design of the ex-post-facto type was employed in the study. Two thousand four hundred (2400) Senior Secondary School Two (SSS2) students comprising 1200 male and 1200 female were sampled for this study. Three (3) validated instruments: Psychological Well-being Scale, Social Economic Status Scale and Peer Group Influence Scale were employed to obtain responses from the participants. Analyses of data were done using descriptive statistics and logistic regression analysis fixed at the .05 significant levels. Results revealed that peer influence (odd ratio = 3.474, Wald value = 29.773, χ2 = 41.523, p< .05), socio-economic background (odd ratio = 3.356, Wald value = 30.211, χ2 = 24.960,p< .05), and gender differentiated (odd ratio = 1.633, Wald value = 25.712, χ2 = 33.005, p< .05) differentiated adolescents’ level of psychological well-being. Age did not differentiate adolescents’ level of Psychological well-being (odd ratio = .301, Wald value = 1.034, χ2 = 2.171, p< .05). The findings showed that all the social factors are potent in differentiating adolescents’ level of psychological well-being. It is concluded that the home environment should be a strong source of support for developing adolescents psychological wellbeing by providing close relationships, strong parenting skills, good communication, and modeling positive behaviour. Therefore, modifications in the home environment should be made more favourable for the enhancement of adolescents’ psychological well-being. Keywords :  Adolescents, Psychological wellbeing, peer influence, Social Economic Status, gender, Secondary Schools.